The role of autoimmune reactions in formation and progressing of Sjogren’s syndrome as systemic damage of organism - Yakimenko, Dmitro (Journal of Education, Health and Sport, 2019)
The purpose of the research was the identification of association of organs and systems damage in Sjogren’s syndrome with the presence of organ-specific and organ-nonspecific autoantibodies. On the basis of complex examination of 21 patients with Sjogren’s syndrome (women age 53,5 ± 0,9 years old) and content determination of wide spectrum of organ-specific and organ-nonspecific autoantibodies we estimated the existence of association between presence of these autoantibodies and clinical manifestations of Sjogren’s syndrome. The received results demonstrate the relationship between the expressiveness of inflammatory manifestations and the content of antibodies to DNA. The expressiveness of salivary glands injuries is associated with content of autoantibodies to salivary glands. The presence of associated diseases is also associated with existence of particular autoantibodies. As in all examined patients with Sjogren’s syndrome was present the digestive tract pathology, it can be assumed that changes in digestive tract wall lead to damage of immune system structures and polyclonal uncontrollable activation of antibodies production.